2011
DOI: 10.1186/1475-2875-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in the kdr allele L1014S in Anopheles gambiae s.s. and phenotypic variability in susceptibility to insecticides in Western Kenya

Abstract: BackgroundMalaria vector control in Africa depends upon effective insecticides in bed nets and indoor residual sprays. This study investigated the extent of insecticide resistance in Anopheles gambiae s.l., Anopheles gambiae s.s. and Anopheles arabiensis in western Kenya where ownership of insecticide-treated bed nets has risen steadily from the late 1990s to 2010. Temporal and spatial variation in the frequency of a knock down resistance (kdr) allele in A. gambiae s.s. was quantified, as was variation in phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
144
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(164 citation statements)
references
References 54 publications
17
144
3
Order By: Relevance
“…Of concern is the possibility of such shifts in A. gambiae s.l. continuing thereby undermining the efficacy of ITNs, a situation that could further deteriorate with the vector reported increase in resistance towards operational pyrethoids (Vulule et al, 1994;Stump et al, 2004;Mathias et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of concern is the possibility of such shifts in A. gambiae s.l. continuing thereby undermining the efficacy of ITNs, a situation that could further deteriorate with the vector reported increase in resistance towards operational pyrethoids (Vulule et al, 1994;Stump et al, 2004;Mathias et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…According to Stump et al (2004) significant differences in kdr gene frequency observed between the large-scale insecticide treated net trial in Asembo area and other areas in western Kenya. Mathias et al, (2011) reported a causal relationship between high ITNs coverage levels and increasing kdr frequency in A. gambiae s.s. in western Kenya.…”
Section: Introductionmentioning
confidence: 96%
“…They reported "a sharp increase in homozygous frequencies from complete absence in both locations initially to 80.5% in Seme in 2008 and 91.7% for Asembo in 2010." 17 In a recent study on the impact of a large scale IRS and ITN campaign in southern Benin, kdr frequencies were also found to have increased, although this was also true for areas in which no planned interventions were implemented, underscoring the effect of the agricultural and household insecticide use on resistance. 18 In east Africa, a similar increase has been observed.…”
Section: L1014s Frequencies Doubled From Approximately 3-4% Inmentioning
confidence: 99%
“…gambiae sensu lato (s.l. ), [14][15][16] a complex of at least eight closely related species including An. gambiae s.s. and An.…”
Section: Introductionmentioning
confidence: 99%